Asymptotic Scenarios for the Proton's Central Opacity: An Empirical Study - Fagundes, D. A. [UNESP]; Menon, M. J.; Silva, P. V. R. G.; Capua, M.; Fiore, R.; Kumericki, K.; Papa, A.; PassekKumericki, K.; Tassi, E.; Vacca, G. P. (Amer Inst Physics, 2015)
We present a model-independent analysis of the experimental data on the ratio X between the elastic and total cross-sections from pp and p (p) over bar scattering in the c.m. energy interval 5 GeV - 8 TeV. Using a novel empirical parametrization for that ratio as a function of the energy and based on theoretical and empirical arguments, we investigate three distinct asymptotic scenarios: either the black-disk (BD) limit or scenarios above and below that limit. Our analysis favors a scenario below the BD, with asymptotic ratio X = 0.36 +/- 0.08.
Keywords: Hadron-induced high- and super-high-energy interactions; total corss-sections; asymptotic problems and properties